Skim milk-coagulating activities of enzymes produced by phycomycetous fungi - Diokno-Palo, Natividad; Palo, Macario; Cunanan, Lourdes F.; Santos, Patrocinio S. (1979)
An exploration of local Phycomycetous fungi flora was conducted, to discover species or strains capable of synthesizing potent milk-clotting enzyme that can be utilized as a substitute for calfs rennet in cheese making from cows milk. Of the sixty seven isolates of saprophytic Phycomycetous fungi belonging to genera Rhizopus, Mucor and Cuninghamella some strains had already been found to produce milk-clotting enzymes. These strains are capable of clotting skim milk in suitable concentrations of calcium ions in 4 to 10 minutes.